Effect of bacterial inoculants on the fermentation of alfalfa silages - Bolsen, K.K.; Bonilla, D.R.; Hart-Thakur, R.A.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The efficacy of 13 commercial bacterial silage inoculants was evaluated on 3rd and 4th cutting alfalfa. All inoculants supplied at least 100,000 colony-forming units (cfu) of lactic acid bacteria (LAB) per gram of ensiled crop, and each inoculant increased the rate and efficiency of the ensiling process. Inoculated alfalfa silages had lower pH values; higher lactic acid contents; and lower acetic acid, ethanol, and ammonia-nitrogen contents than control (untreated) silages. The addition of dextrose (fermentable substrate) in combination with a bacterial inoculant improved the quality of the fermentation phase in both cuttings of alfalfa.
Keywords: Beef; Silage; Innoculant; Fermentation; Alfalfa